LOCAL COMMUNITY-BASED SUSTAINABLE TOURISM DEVELOPMENT TOWARDS COMMUNITY WELFARE - Mauliyanti, Anita; Sujianto, Agus Eko; Nurrohman, Dede (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Local community-based sustainable tourism is an important strategy in developing a tourism sector that is oriented towards community welfare. This research aims to explore a sustainable tourism development model that involves local communities as the main actors in the management and development of tourist destinations. The method used is literature review by analyzing various previous studies regarding policies, strategies, and social, economic and environmental impacts of community-based tourism. The study results show that the active involvement of local communities in tourism planning and management can improve economic welfare through employment opportunities and micro-enterprises. Apart from that, the community-based sustainable tourism model also contributes to cultural and environmental preservation by instilling conservation values and local wisdom. However, there are challenges that need to be overcome, such as lack of human resource capacity, capital and access to global markets. Therefore, synergy is needed between the government, tourism industry players and the community in creating an inclusive and sustainable tourism ecosystem. With the right approach, community-based tourism development can be a catalyst in improving community welfare and preserving cultural heritage and the environment.